The use of social media among health care professionals within an online postgraduate diabetes diploma course. (January 2014) - Lipp, A; Davis, RE; Peter, R; Davies, JS
Abstract: Social media is a rapidly growing arena through which members of the health care community can communicate between themselves as well as inform and educate patients. We assessed the impact of certain types of social media (YouTube and Twitter) among a group of health care professionals (HCPs) studying for a diploma in diabetes with the University of South Wales. As part of a module of the diabetes diploma, HCPs were tasked with using social media (Twitter and YouTube) to communicate information on diabetes and metrics were assessed on its impact. In respect of Twitter accounts, interactivity was assessed through number of 'tweets' users posted, the number of 'followers' that each account attracted together with the number of people that the user 'followed'. For YouTube videos, we collected data on the length of video, the number of views each received as well as 'likes' or 'dislikes'. We also asked all students to complete a voluntary questionnaire on their subjective feelings regarding their experience with social media. Of 89 subjects, 27 developed YouTube videos and 62 set up Twitter accounts (in the event of a subject using both Twitter and YouTube, only their YouTube data are used). Average video length was 7 minutes 10 seconds, with videos viewed from 20–1274 times up to August 2012. Sixty‐two Twitter accounts were established with an average of 77 tweets, average of 34 'followers' and an average of 49 'following'. Thirteen (15%) HCPs responded to a feedback questionnaire, four having selected YouTube and nine, Twitter. Eight students expressed apprehension before embarking on the task but all expressed a sense of achievement and confidence in use of social media upon completion. Fifty (81%) HCPs stopped using Twitter within six months of completing the module, although Twitter activity continued among 12 (19%) HCPs. This study reveals a successful uptake and communication of a professional message to a wider audience through Twitter and YouTube among social media‐naïve HCPs studying for a postgraduate diploma in diabetes. Despite initial apprehension, HCPs felt confident in using social media to convey the message with continuing use of social media beyond the confines of the course. Copyright © 2014 John Wiley & Sons.